Informational Competence: A Relevant Conception to Take into Consideration in Higher Education - María Elinor Dulzaides Iglesias; Ana María Molina Gómez (Medisur)
Competence is today a relevant conception to take into consideration. It implies more integration between strategy, study system, work and organizational culture, along with information management and knowledge. It offers potential to people and their development. The management of roles by competences is focused in development; it looks for what people are capable of doing in the future. Present day scenarios demand for a new educative arquitecture following learning for life, what implies: teaching to learn and, overall, to use information in an adequate manner. In this work we lay stress on the topic as an essential element to consider in Higher Medical Education, given the constant changes in medicine and the need for knowledge and skills for an adequate practice.